Relationship of Covid-19 Pandemic on Performance and Internal Operation of The Airline - Dadan Iskandar; Arviansyah . (The Asian Journal of Technology Management (AJTM), 2021)
Abstract. Air transport business is challenged to oversee their performance and operations to preserve their business presence within the COVID-19 widespread. It is fundamental to distinguish the suitable performance and operation and their relationship with the pandemic. In this way, we used the indicators to employ a systematic literature review and experts’ point of view to select and group suitable indicators to address the literature gap. Twenty performance and internal operations indicators are identified and redefined from the review. The Delphi method’s result suggests eight indicators categorized in airline performance indicators and seven indicators categorized in internal operation indicators. We investigate the relationship of COVID-19 pandemic on the selected indicators using SmartPLS based on fifty-two weeks performance, and operation report of one of full-service airline started from 08 March 2020 until 28 February 2021. It can be deduced that the COVID-19 pandemic has a significant and negative influence on the airline’s performance. This study fills the gap by synthesizing and creating suitable and comprehensive performance and operation indicators of air transport carriers in a pandemic situation and their relationships. Finally, this study provides an invaluable point for analyzing the air transport carrier industries in a pandemic to maximize performance through profitability and load factors indicators.Keywords:  Airline, Pandemic, Performance, Operation